2012
DOI: 10.1016/j.jmoldx.2012.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Detection of High-Frequency and Novel DNMT3A Mutations in Acute Myeloid Leukemia by High-Resolution Melting Curve Analysis

Abstract: DNA methyltransferase 3A (DNMT3A) is mutated in a subset of de novo acute myeloid leukemia patients and is associated with poor overall and event-free survival. Because routine Sanger sequencing of the 23 DNMT3A exons is impractical in clinical laboratories, we developed a high-throughput method using highresolution melting (HRM) analysis, which identifies sequence variants by detecting subtle changes in the melting patterns of mutant DNA in comparison with WT sequences. DNA from 104 acute myeloid leukemia pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
1
18
1
1
Order By: Relevance
“…[19][20][21] Briefly, genomic DNA was Original Article extracted from bone marrow aspirates or peripheral blood. [19][20][21] Briefly, genomic DNA was Original Article extracted from bone marrow aspirates or peripheral blood.…”
Section: Response Criteria and Statistical Analysismentioning
confidence: 99%
“…[19][20][21] Briefly, genomic DNA was Original Article extracted from bone marrow aspirates or peripheral blood. [19][20][21] Briefly, genomic DNA was Original Article extracted from bone marrow aspirates or peripheral blood.…”
Section: Response Criteria and Statistical Analysismentioning
confidence: 99%
“…Eleven additional samples were sequenced on the MiSeq instrument in parallel (blind) with routinely used platforms, including Sanger sequencing, pyrosequencing and fragment analysis by capillary electrophoresis, performed as described previously. [28][29][30] To confirm mutations detected in regions covered by TSACP but not by preexisting assays in our laboratory (AmpliSeq cancer panel, Sanger or pyro sequencing), 42 new Sanger sequencing assays were also developed.…”
Section: Tumor Samples and Sequencing Platformsmentioning
confidence: 99%
“…89 Although previous studies clearly pointed to an oncogenic role of DNMT3A in cancer, the recent discovery of genetic mutations of DNMT3A in acute myeloid leukemia (AML) suggested that its role in cancers may be more complex than was previously believed. [11][12][13][14][15][16][17][18][19][20][21][22][23] These highly recurrent DNMT3A mutations were closely associated with poor outcome in patients with AML. However, the functional implications of these mutations are still poorly understood.…”
Section: The Dual Roles Of Dnmt3a In Cancermentioning
confidence: 99%
“…10 However, several inactivating mutations of DNMT3A in myeloid malignancies [11][12][13][14][15][16][17][18][19][20][21][22][23] and loss of DNMT3A activity at advanced tumor stages 24 were recently identified. In addition, novel roles of DNMT3A in the hematopoiesis system 25 and in the age-related decline of cognition 26 have been revealed.…”
Section: Introductionmentioning
confidence: 99%